The vagility of an invasive species, the grey squirrel (Sciurus carolinensis) : studies of population genetic structure, control and recolonisation, range expansion and pox virus - McGoldrick, Micheal S. (Trinity College (Dublin, Ireland). Department of Zoology, 2011)
About a dozen grey squirrels were introduced to Castleforbes, Co. Longford in 1911 and have since expanded their range, almost exclusively to counties east of the Shannon, at a mean rate of 1.94km/year.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin